Models, Methods and Tools of Optimizing Costs for Development of Clusterized Organizational Structures in Construction Industry - Mykytas, M; Terenchuk, S; Zhuravska, N (International Journal of Engineering and Technology, 2018)
The mission of this research shall be studying the models and methods of evaluation of the expected costs to be used in economic efficiency optimization of clusterized organizational structures in construction industry. It comprises analysis of models and methods of simulation of the development of complex models under fuzzy conditions. It shows benefits and drawbacks of realizing the scenario approach based on econometric semi-linear dynamic equations. The optimization of costs has been proposed to be performed based on simulation modelling of various scenarios of development of clusterized organizational structures of construction branch. The results of simulation can be useful in feasibility demonstrations of the long-term plans and strategies of development on various stages of structures’ life cycle. The mathematical basics and scheme of forming the minimum costs for providing the best strategy of development of clusterized organizational structure.  The academic novelty of work consists in developing the rationale of application of fuzzy neuron boundaries. The responsibility for the development of fuzzy rules in order to form system fuzzy databases shall be vested in experts.